Utilization Patterns of IV Iron and Erythropoiesis Stimulating Agents in Anemic Chronic Kidney Disease Patients: A Multihospital Study. (19th April 2012) - Joshi, Avani D.; Holdford, David A.; Brophy, Donald F.; Harpe, Spencer E.; Mays, Darcy; Gehr, Todd W. B.
Abstract : Intravenous (IV) iron and Erythropoiesis Stimulating Agents (ESAs) are recommended for anemia management in chronic kidney disease (CKD). This retrospective cohort study analyzed utilization patterns of IV iron and ESA in patients over 18 years of age admitted to University Health System Hospitals with a primary or secondary diagnosis of CKD between January 1, 2006 to December 31, 2008. A clustered binomial logistic regression using the GEE methodology was used to identify predictors of IV iron utilization. Only 8% ( n = 6678) of CKD patients on ESA therapy received IV iron supplementation in university hospitals. Those receiving iron used significantly less amounts of ESAs. Patient demographics (age, race, primary payer), patient clinical conditions (admission status, severity of illness, dialysis status), and physician specialty were identified as predictors of IV iron use in CKD patients. Use of IV iron with ESAs was low despite recommendations from consensus guidelines. The low treatment rate of IV iron represents a gap in treatment practices and signals an opportunity for healthcare improvement in CKD anemic patients.